Exploring stingless bees and meliponiculture in Nepal - Nischal Kafle; Avishek Giri; Astha Dhakal; Abhishek Bhattarai; Aavash Shrestha (ACTA Apicola Brasilica)
Stingless bees are crucial pollinators with significant cultural and ecological roles. They are essential for the pollination of various plants, contributing to biodiversity and the health of ecosystems. These bees also play a vital role in sustaining agricultural productivity by enhancing crop yields through their pollination services. Meliponiculture, the practice of keeping stingless bees for honey production and pollination, presents a viable livelihood option for rural communities, offering economic benefits and promoting sustainable agricultural practices. Despite their importance, stingless bees have been relatively understudied, and their unique biological traits, nesting behavior, and ecological roles remain underexplored. The lack of research has led to an absence of specific policies addressing their conservation or management in Nepal. This gap in policy and knowledge hampers efforts to protect these essential pollinators and their habitats. Effective conservation strategies and policy development are urgently needed to safeguard native stingless bee populations, ensure their continued ecological contributions, and support local livelihoods through sustainable meliponiculture practices.